2021
DOI: 10.1249/mss.0000000000002828
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness and Chemotherapy Tolerance in Patients with Early-Stage Breast Cancer

Abstract: You will be contacted as soon as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…An absolute percentage error of 10% for VȮ 2 could for instance result in a fireman not meeting a predefined VȮ 2max value required to continue their profession 11 and patients not meeting a predefined VȮ 2max value advised to undergo major surgery 12 or delay medical treatment. 13 Conversely, it could also lead to individuals falsely meeting the criteria, which increases subsequent during the profession in the case of the fireman, or during surgery for patients. For world-class athletes, even small differences in VȮ 2max (e.g., <1.5%) could lead to relevant inaccuracies in performance predictions (e.g., 64 ), or talent identification.…”
Section: Perspectivementioning
confidence: 99%
“…An absolute percentage error of 10% for VȮ 2 could for instance result in a fireman not meeting a predefined VȮ 2max value required to continue their profession 11 and patients not meeting a predefined VȮ 2max value advised to undergo major surgery 12 or delay medical treatment. 13 Conversely, it could also lead to individuals falsely meeting the criteria, which increases subsequent during the profession in the case of the fireman, or during surgery for patients. For world-class athletes, even small differences in VȮ 2max (e.g., <1.5%) could lead to relevant inaccuracies in performance predictions (e.g., 64 ), or talent identification.…”
Section: Perspectivementioning
confidence: 99%
“…We speculate that patients with T1N0M0-stage disease can benefit from postoperative adjuvant chemotherapy because of its killing effect on early microscopic metastases in the liver, blood, or lymph nodes. In addition, some studies have attributed the benefits of adjuvant chemotherapy to the better physical condition and chemotherapy tolerance of patients with early-stage tumors and the higher completion rate of adjuvant chemotherapy [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 Similarly, Groen et al reported that lower pretreatment physical fitness was associated with lower odds of achieving ≥85%, even after correcting for age. 13 Few studies have evaluated the effect of exercise on RDI in mixed cancer sites, rather, focusing on a single cancer site. 9 However, cancer exercise physiologists routinely work with many cancer sites requiring studies that reflect the real-world value and practical realities of working in a clinical cancer care setting.…”
Section: Introductionmentioning
confidence: 99%